How Do Banks Determine Capital? Empirical Evidence for Germany - Martin Weber; Volker Kleff (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
This paper examines how capital is determined by German banks. We analyse whether the determinants found in the previous empirical literature hold for the special German banking sector with its three characteristic banking groups of savings banks, cooperative banks and other banks. On the basis of a unique data set of nearly all German banks between 1992 and 2001 provided by the Deutsche Bundesbank, we apply the generalised method of moments (GMM) within a dynamic panel data framework. The results largely confirm the findings for other countries, but show considerable differences between the three German banking groups.
Keywords: G32; C23; G21; 330; Bank capital; portfolio risk; banking regulation; panel data; GMM; Bank; Eigenkapital; Kapitalstruktur; Bankrisiko; Eigenkapitalvorschriften; Basel II; Schätzung; Deutschland